Culture-Independent Evaluation of Nonenveloped-Virus Infectivity Reduced by Free-Chlorine Disinfection - Sano, Daisuke (Appl Environ Microbiol, 2015)
The inability of molecular detection methods to distinguish disinfected virions from infectious ones has hampered the assessment of infectivity for enteric viruses caused by disinfection practices. In the present study, the reduction of infectivity of murine norovirus S7-PP3 and mengovirus vMC0, surrogates of human noroviruses and enteroviruses, respectively, caused by free-chlorine treatment was characterized culture independently by detecting carbonyl groups on viral capsid protein. The amount of carbonyls on viral capsid protein was evaluated by the proportion of biotinylated virions trapped by avidin-immobilized gel (percent adsorbed). This culture-independent approach demonstrated that the percent adsorbed was significantly correlated with the logarithm of the infectious titer of tested viruses. Taken together with the results of previous reports, the result obtained in this study indicates that the amount of carbonyls on viral capsid protein of four important families of waterborne pathogenic viruses, Astroviridae, Reoviridae, Caliciviridae, and Picornaviridae, is increased in proportion to the received oxidative stress of free chlorine. There was also a significant correlation between the percent adsorbed and the logarithm of the ratio of genome copy number to PFU, which enables estimation of the infectious titer of a subject virus by measuring values of the total genome copy number and the percent adsorbed. The proposed method is applicable when the validation of a 4-log reduction of viruses, a requirement in U.S. EPA guidelines for virus removal from water, is needed along with clear evidence of the oxidation of virus particles with chlorine-based disinfectants.